Developing Innovations Leveraging the Cultural Capital of the Hmong Ethnic Group in Phop Phra District Tak Province - Wongvilarat, Sirinee (Journal of Posthumanism, 2025)
This research project, titled “Innovation Development from Hemp Based on the Cultural Capital of the Hmong Ethnic Group in Phop Phra District, Tak Province,” examines the potential of indigenous knowledge and cultural heritage as drivers for innovation and sustainable development. The study aimed to: (1) explore the cultural practices and traditional knowledge of the Hmong people in hemp cultivation, textile weaving, and product development; (2) co-develop hemp-based products utilizing all parts of the plant including roots, stems, and leaves through collaboration between educational institutions and local partners; and (3) enhance the capacity of entrepreneurs and cultural innovators in knowledge communication and product development. Using the Participatory Action Research (PAR) approach, the study involved local artisans, entrepreneurs, youth, returnees, and cultural innovators. It was guided by three principles: Engage (stakeholder participation), Enrich (cultural significance), and Enhance (capacity building). Findings revealed that hemp holds strong cultural and spiritual significance in the Hmong community. Considered a sacred plant, its cultivation and usage span the entire life cycle and are deeply embedded in Hmong traditions. Knowledge is passed down through elders and schools, and traditional fiber processing and weaving reflect distinctive cultural wisdom. The project led to the development of diverse hemp-based products that merged traditional craftsmanship with modern innovation. A dedicated website (www.hemp-tak.com) and the “Popkan” brand were launched, enhancing local business identity. A cultural mapping initiative and related publication documented Hmong hemp heritage, including routes, customs, cuisine, and rituals. A learning center, “Hemp and the Hmong Way,” was also established to support education, marketing, and community engagement. Lastly, a Social Return on Investment (SROI) analysis showed that every 1 baht invested yielded a social value of 3.22 baht, indicating strong social impact and long-term benefits